1967
DOI: 10.1113/jphysiol.1967.sp008386
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal actions of the heart and of lungs on the isolated kidney

Abstract: SUMMARY1. An hormonal influence of the heart on the isolated kidney has been demonstrated by insertion of hearts into pump-oxygenator circuits during renal perfusions.2. This hormone is a steroid which is secreted from the heart into the cardiac venous blood in response to reduction in venous input. The steroid is extractable from heart muscle.3. The actions of the cardiac steroid resemble those of aldosterone but are of shorter latency. Renal blood flow (R.B.F.) and glomerular filtration rate (G.F.R.) rise; u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Extra-adrenal aldosterone production and tissue repair Some 40 years ago, Lockett et al [105][106][107][108][109][110] reported that the beating heart and contracting soleus muscle of cats were sites of steroid generation; the substance resembled 18-D-aldosterone.They found this molecule in coronary venous blood and demonstrated its ability to promote renal salt and water retention. These findings lay fallow until the past decade, when Takeda 111,112 identified the mRNA expression of ALDO synthase (CYP11B2) and ALDO production in rodent vascular tissue.…”
Section: Central Actions Of Aldosteronementioning
confidence: 99%
“…Extra-adrenal aldosterone production and tissue repair Some 40 years ago, Lockett et al [105][106][107][108][109][110] reported that the beating heart and contracting soleus muscle of cats were sites of steroid generation; the substance resembled 18-D-aldosterone.They found this molecule in coronary venous blood and demonstrated its ability to promote renal salt and water retention. These findings lay fallow until the past decade, when Takeda 111,112 identified the mRNA expression of ALDO synthase (CYP11B2) and ALDO production in rodent vascular tissue.…”
Section: Central Actions Of Aldosteronementioning
confidence: 99%
“…Corticosterone, cortisone, deoxycorticosterone, hydrocortisone and Reichstein's substance S were obtained commercially from Sigma Chemical Company, St Louis, U.S.A. Biological Heart-lung preparations were made and kidneys were perfused by heart-lung or pumpoxygenator circuits as previously described (Lockett, 1957(Lockett, , 1966(Lockett, , 1967. The blood used to fill the perfusion circuits was collected and all preparations were made in cats initially anaesthetized with ether and then made spinal by destruction of the brain either during temporary occlusion of the carotids (intact donors) or after ligature of the brachiocephalic and L. subclavian arteries (headless donors).…”
Section: Reference Steroidsmentioning
confidence: 99%
“…Ability to synthesize HS may therefore be a property of all striped muscle. The rate of secretion of HS may not, however, be controlled solely by the frequency of depolarization, but may also be influenced by changes in the contractile state (Lockett, 1967). Hence the present purpose was to determine the influence of fibre length, of change in external work, of digitalization and of procaine on the secretion of HS by the cat heart.…”
Section: Introductionmentioning
confidence: 99%
“…A substance similar to the 18-monoacetate of D-aldosterone (Lockett, 1967;Ilett & Lockett, 1968;Knox & Lockett, 1969) in its chromatographic and biological properties is secreted into the coronary circulation by the cat heart in vivo (Lockett & Retallack, 1970). Positive correlation is demonstrable between heart rate and the concentration of this substance (HS) in the venous blood entering the R. atrium from the coronary sinus.…”
Section: Introductionmentioning
confidence: 99%